Efficient Algorithms for Conducting Stochastic Dominance Tests on Large Numbers of Portfolios: A Comment - Frankfurter, George M.; Phillips, Herbert E. (Journal of Financial and Quantitative Analysis, 1975)
George M. Frankfurter, Herbert E. Phillips, Efficient Algorithms for Conducting Stochastic Dominance Tests on Large Numbers of Portfolios: A Comment, The Journal of Financial and Quantitative Analysis, Vol. 10, No. 1 (Mar., 1975), pp. 177-179